Holocene evolution of lakes in the forest-tundra biome of northern Manitoba, Canada. (1st March 2017) - Hobbs, William O.; Edlund, Mark B.; Umbanhowar, Charles E.; Camill, Philip; Lynch, Jason A.; Geiss, Christoph; Stefanova, Vania
Abstract: The late-Quaternary paleoenvironmental history of the western Hudson Bay region of Subarctic Canada is poorly constrained. Here, we present a regional overview of the post-glacial history of eight lakes which span the forest-tundra biome in northern Manitoba. We show that during the penultimate drainage phase of Lake Agassiz the lake water had an estimated pH of ∼6.0, with abundant quillwort ( Isöetes spp.) along the lakeshore and littoral zone and some floating green algae ( Botryococcus spp. and Pediastrum sp.). Based on multiple sediment proxies, modern lake ontogeny in the region commenced at ∼7500 cal yrs BP. Pioneering diatom communities were shaped by the turbid, higher alkalinity lake waters which were influenced by base cation weathering of the surrounding till following Lake Agassiz drainage. By ∼7000 cal yrs BP, soil development and Picea spp. establish and the lakes began a slow trajectory of acidification over the remaining Holocene epoch. The natural acidification of the lakes in this region is slow, on the order of several millennia for one pH unit. Each of the study lakes exhibit relatively stable aquatic communities during the Holocene Thermal Maximum, suggesting this period is a poor analogue for modern climatic changes. During the Neoglacial, the beginning of the post-Little Ice Age period represents the most significant climatic event to impact the lakes of N. Manitoba. In the context of regional lake histories, the rate of diatom floristic change in the last 200–300 years is unprecedented, with the exception of post-glacial lake ontogeny in some of the lakes. For nearly the entire history of the lakes in this region, there is a strong linkage between landscape development and the aquatic ecosystems; however this relationship appears to become decoupled or less strong in the post-LIA period. Significant 20th century changes in the aquatic ecosystem cannot be explained wholly by changes in the terrestrial ecosystem, suggesting that future changes to the lakes of N. Manitoba will be strongly influenced by direct climatic effects to the lakes. Graphical abstract: Highlights: Glacial Lake Agassiz had a turbid water column with an estimated pH of 6.0 Base cation weathering of surrounding till shapes pioneering diatom communities. Lake morphology and catchment vegetation control aquatic response to climate. The HTM is a poor analogue for future climate-driven ecological change. The rate of floristic change in the last 200–300 years is unprecedented.